ANCA negative eosinophilic granulomatosis with polyangiitis: sometimes it really IS vasculitis. (23rd December 2015) - Tyagi, Niharika; Maheswaran, Tim; Wimalaratna, Sunil
Abstract : A 21-year-old woman, with a background of asthma, presented to medical admissions ward, with diarrhoea and vomiting; the clinical picture during her admission evolved to include acute shortness of breath, seizures, unsteadiness, low mood and apathy. Investigations revealed pericardial, pleural effusions, myocardial infiltration and vasculitic lesions in the brain. Although serological tests for autoantibodies were negative, an eventual diagnosis of eosinophilic granulomatosis with polyangiitis, formerly known as Churg-Strauss syndrome, was performed based on the clinical picture. The multiorgan involvement meant that the initial diagnosis and effective management required multidisciplinary input from cardiology, neurology, rheumatology, psychiatry, immunology and occupational and physiotherapy.